Ethics in nursing education according to the graduating nursing la Brazilian public institution - Ranuz, Cristina; Vieira de Almeida, Débora; Contim, Divanice (O Mundo da Saúde, 2017)
This study aims to investigate the views of beginners and graduating students from the nursing graduation college on ethics in nursing education. According to this purpose, a qualitative research was conducted with nursing students from the second and eighth semesters of a public university located in Triângulo Mineiro (Minas Gerais, Brazil). Discourses of the collective subject were analyzed according to content analysis is. Results: Two categories emerged from the discourse of the subject of the second half (Attitude relational scene of life and posture that underlies professional practice) and two in the eighth (limits set by ethics and attitudes in interpersonal relationships). For nursing students (freshmen and seniors) the ethics is important in the graduation process, not restricted to technical and scientific progress, but it involves personal development as subjects entered the academic learning process.